2004
DOI: 10.1182/blood-2003-11-3967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the proteasome inhibitor PS-341 on tumor growth in HTLV-1 Tax transgenic mice and Tax tumor transplants

Abstract: IntroductionHuman T-cell leukemia/lymphotropic virus type 1 (HTLV-1) infection is present in 10 to 20 million people worldwide. 1,2 HTLV-1 infection results in 2 different diseases: adult T-cell leukemia/lymphoma (ATLL or ATL) and the neurologic disorder tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/ HAM). 3,4 Although the epidemiology and clinical characteristics of HTLV-1 infection are defined, the molecular mechanisms used by the virus to establish persistent infection and subsequently prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…The proteasome inhibitor, borteozomib, inhibits the degradation of the inhibitor of NF-kB, IkBa. It was shown to inhibit NF-kB activation in ATL cells and Tax transgenic tumor cells in culture and in mouse transplantation studies (Tan and Waldmann, 2002;Satou et al, 2004;Mitra-Kaushik et al, 2004b). In several of these studies, the majority of the cell death was found to be due to apoptosis.…”
Section: Therapeutic Modalities In Htlv-1 Animal Modelsmentioning
confidence: 99%
“…The proteasome inhibitor, borteozomib, inhibits the degradation of the inhibitor of NF-kB, IkBa. It was shown to inhibit NF-kB activation in ATL cells and Tax transgenic tumor cells in culture and in mouse transplantation studies (Tan and Waldmann, 2002;Satou et al, 2004;Mitra-Kaushik et al, 2004b). In several of these studies, the majority of the cell death was found to be due to apoptosis.…”
Section: Therapeutic Modalities In Htlv-1 Animal Modelsmentioning
confidence: 99%
“…One of its mechanisms is suppression of the NF-κB pathway by inhibiting the proteasomal degradation of IκB protein. Several groups have shown that Bortezomib is effective against ATL cells both in vitro and in vivo (Mitra-Kaushik et al 2004). The sensitivity to Bortezomib is well correlated with the extent of NF-κB activation.…”
Section: Atl Treatment: Current State and New Strategiesmentioning
confidence: 95%
“…Inhibitors of NF-κB activation, including sodium salicylate and cyclopentenone prostaglandins, blocked tumor cell proliferation in culture and sensitized the cells to γ irradiation. A proteasome inhibitor, PS-341 or bortezomib (Velcade), which blocks degradation of the inhibitor of NF-κB, also inhibited tumor cell proliferation in culture and sensitized cells to γ irradiation-induced apoptosis (29). Moreover, PS-341 inhibited tumor cell proliferation in vivo in transgenic mice and mice transplanted with Tax transgenic tumor cells.…”
Section: Tax Transgenic Micementioning
confidence: 98%